2018
DOI: 10.1002/cptc.201800155
|View full text |Cite
|
Sign up to set email alerts
|

Thiol−Ene Coupling in a Continuous Photo‐Flow Regime

Abstract: Photoinitiated thiol−ene chemistry is a promising technique for use in chemical synthesis and related sciences. In view of scaling, the process was successfully transferred to a continuous flow regime with compelling results in terms of selectivity, efficiency, and productivity. A series of selected thiols and enes were reacted using 2,2‐dimethoxy‐2‐phenylacetophenone as radical initiator to respond to the 365 nm UV‐LED source. Process parameters were evaluated and chemical cross‐reactivity of the different su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Therefore, it appeared advantageous to employ a photocatalyst, a common practice for this photochemical reaction. For thiol–ene reactions in continuous flow, 2,2-dimethoxy-2-phenylacetophenone (DMPA) as a photoinitiator or Ru­(bpy) 3 (PF 6 ) 2 as a photocatalyst have been reported. While Ru­(bpz) 3 (PF 6 ) 2 has been reported to catalyze the thiol–ene reaction of similar thiol substrates such as cysteine methyl ester via a single electron transfer mechanism, it was important to avoid expensive metal catalysts in our approach. Therefore, to accelerate this reaction, we envisioned employing 9-fluorenone (9-FL) as an inexpensive photocatalyst .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it appeared advantageous to employ a photocatalyst, a common practice for this photochemical reaction. For thiol–ene reactions in continuous flow, 2,2-dimethoxy-2-phenylacetophenone (DMPA) as a photoinitiator or Ru­(bpy) 3 (PF 6 ) 2 as a photocatalyst have been reported. While Ru­(bpz) 3 (PF 6 ) 2 has been reported to catalyze the thiol–ene reaction of similar thiol substrates such as cysteine methyl ester via a single electron transfer mechanism, it was important to avoid expensive metal catalysts in our approach. Therefore, to accelerate this reaction, we envisioned employing 9-fluorenone (9-FL) as an inexpensive photocatalyst .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, light-absorbing chromophores on one or both reactive groups limit the ability to obtain optically thin reactions without extremely low concentrations or very small volumes. Flow reactors, as compared to batch systems, avoid constraints associated with light attenuation and allow for simple scale-up of photoinitiated polymerizations, which can be combined with orthogonal reactions (e.g., thermally driven polymer modifications) within the reactor to produce complex products in unprecedented yield and in essentially one step . Using a photoinduced Diels–Alder cycloaddition between o -quinodimethane thioether and maleimide, Feist et al demonstrated full conversion of starting materials in a photoflow polymerization in aqueous solution and catalyzed by visible light from LEDs, modeling remarkable reagent and catalyst sustainability in a highly efficient polymerization system …”
Section: Applicationsmentioning
confidence: 99%
“…For thiol-ene reactions in continuous flow, 2,2-dimethoxy-2-phenylacetophenone (DMPA) as photoinitiator or Ru(bpy)3(PF6)2 as photocatalyst have been reported. [26][27][28] While Ru(bpz)3(PF6)2 has been reported to catalyze the thiol-ene reaction of similar thiol substrates such as cysteine methyl ester via a single electron transfer (SET) mechanism, 29 it was important to avoid expensive metal catalysts in our approach. Therefore, to accelerate this reaction, we envisioned employing 9-fluorenone (9-FL) as inexpensive photocatalyst.…”
Section: Scheme 3 Thiol-ene Reaction Of Cysteamine Hydrochloride With...mentioning
confidence: 99%